A new species of heterochelous tanaidacean Tanaissus (Paratanaoidea: Tanaissuidae) from the north-west Iberian Peninsula - Esquete, Patricia; Rubal, Marcos (Zootaxa, 2015)
A new species of tanaidomorph, Tanaissus bamberi, is described from the north-western region of the Iberian Peninsula. Its most remarkable character is the presence of morphologically different right and left chelae in the males. The species occurs sympatrically with T. lilljeborgi, mainly in intertidal and subtidal sediments of medium to muddy sands typical of fully marine and estuarine salinities.